A study of epidemiological, etiological, and clinicopathological factors in periocular hyperpigmentation - Manas Chatterjee; Bhabendra Suwal; Ajay Malik; Biju Vasudevan (Wolters Kluwer Medknow Publications, 2018)
Background: Periocular darkening, popularly known as "dark circles," is a common condition globally. Pigment deposition, shadowing due to laxity, superficial location of vasculature and prominent nasojugal groove are recognized causative factors. Very few studies exist on its clinicopathological correlation, especially in the Asian population. Materials and Methods: Eighty-two consecutive patients attending skin outpatient department (OPD) with periocular hyperpigmentation (POH) who agreed to follow the study protocol were included in this descriptive study, conducted in Maharashtra, India. They were evaluated clinically and also investigated with histopathology, special staining and immunohistochemistry of the periocular skin to study the various factors involved in the pathogenesis. Results: 19.51% of the patients had a positive family history of POH, 90% gave history of exhaustion of periocular muscles, 41.46% had anemia, 8.54% gave history of aggravation during pregnancy and 7.32% had menstrual irregularities. Laxity of skin was present in 82.92% patients, visible veins in 50%, and sunken eyes with prominent infraorbital rim and shadowing in 26.82%. Periocular darkening due to pigment was present in only 17% patients, with mixed dermoepidermal pigmentation being present in majority (70.73%). Clinicopathological concordance was significant in case of dermal pigmentation (Fisher's exact test P-value <0.05) in contrast to epidermal. Conclusion: Periocular darkening was predominantly not due to pigment, but rather due to cutaneous laxity and vascular visibility through thin skin. Most of them with pigment had it in the dermis. Clinical dermal pigmentation correlated well with histology, unlike epidermal pigmentation. Iron and amyloid were not significant as etiological factors in our patients.